A Pseudoaneurysm of Aberrant Right Subclavian Artery Caused by Esophageal Stent Placement Because of Esophageal Stricture After Endoscopic Submucosal Dissection. Issue 5 (October 2019) - Zheng, Shiqin; Wang, Xiaosong; Chen, Shuang; Wei, Jianming; Wei, Zhiqing; Miao, Lin; Zhang, Xiuhua
Abstract : A 67-year-old man who received endoscopic submucosal dissection for an early squamous esophageal cancer was hospitalized for dysphagia. The mucosal defect was over three quarters of the circumference, and the distal edge of the resection scar formed the stenosis after 8 months. After experiencing conservative treatment, probe expansion, and esophageal stent placement, the symptom of deglutition disorder in the patient was improved, but persistent hemorrhage and progressive anemia occurred in the short term. An enhanced neck and chest computed tomography (CT) showed a contrast agent leaked from the aberrant right subclavian artery to the esophagus. A pseudoaneurysm of the aberrant right subclavian artery and subclavian artery-esophageal fistula were diagnosed by CT angiography. Although false aneurysms developing after iatrogenic injury and trauma have been reported, those caused by esophageal stent placement because of esophageal stricture after endoscopic submucosal dissection have not. When persistent hemorrhage and progressive anemia develop after esophageal stent placement, an enhanced CT should be performed to exclude the false aneurysm.